Política, sociedad y religión en Arequipa: una mirada desde el laicado católico militante (1885- 1919) - Iberico Ruiz, Rolando (2021)
The article analyzes the relationship between religion, society and politics from the perspective of militant Catholic laity in Arequipa. The study identifies two paradigms to understand this relationship influenced by the episcopal understanding of the socio-political context. The first paradigm was characterized by the desire to «Christianize» the country’s social and political institutions, that is, to monopolize the state institutions. The second paradigm, the Catholic societies sought to maintain the presence of Catholicism in society and politics by inter-vening in them. Through the public actions, the Catholic laity gave an implicit recognition of the emerging plurality of social and political options in Arequipa.